2018
DOI: 10.1002/uog.19023
|View full text |Cite
|
Sign up to set email alerts
|

Home blood‐pressure monitoring in a hypertensive pregnant population

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 27 publications
0
81
0
7
Order By: Relevance
“…With the advent of smartphones and evolving technologies, home blood pressure monitoring may become the mainstay of the management of hypertensive diseases both during the pregnancy and postnatally in the community [37, 38]. This will hopefully achieve better blood pressure control and reduce the need for as many hospital visits without jeopardising maternal and fetal outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the advent of smartphones and evolving technologies, home blood pressure monitoring may become the mainstay of the management of hypertensive diseases both during the pregnancy and postnatally in the community [37, 38]. This will hopefully achieve better blood pressure control and reduce the need for as many hospital visits without jeopardising maternal and fetal outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…This will hopefully achieve better blood pressure control and reduce the need for as many hospital visits without jeopardising maternal and fetal outcomes [38]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential benefits of HBPM in pregnancy include earlier detection of pre-eclampsia, convenience for the pregnant woman and reduced healthcare costs, as well as increased compliance with and acceptance of monitoring [8][9][10][11] . Our recent work has demonstrated that HBPM reduces the number of hospital visits without compromising maternal and fetal outcomes 9 . Furthermore, HBPM was found to be cost-effective, with an average saving per week of £286.53 in the group of women following HBPM using a dedicated app, compared with those undergoing traditional monitoring at the hospital/clinic 8 .…”
Section: Introductionmentioning
confidence: 99%